Binaural sound source localization based on weighted template matching - Liu, Hong; Sun, Yongheng; Yang, Ge; Chen, Yang (CAAI Transactions on Intelligence Technology, 2021)
In robot binaural sound source localization (SSL), locating the direction of the sound source accurately in the shortest time is important. It refers to the algorithm complexity, but even more to the shortest duration of the required signal. A novel binaural SSL method based on feature and frequency weighting is proposed. More specifically, in the training stage, the direction‐related interaural cross‐correlation function(CCF) and interaural intensity difference(IID) in each frequency band are calculated under noiseless conditions, which are considered the templates. In the testing stage, first the cosine similarities between the CCF and IID of the test signal and templates are calculated in all features and frequency bands. Then, the direction likelihood can be obtained by weighting the similarities. Finally, the direction with maximum likelihood is specified as the direction of the sound source. Experiments were carried out on CIPIC dataset subject 003 with different noises in the noisex‐92 dataset and demonstrated that the method can accurately locate the sound source with a short signal duration.